Motivation – Are There Limits to What Can be Achieved? - Sukma Putra (Bina Nusantara University, 2012)
Motivation is the underlying reason for an act committed by an individual. A highly motivated person is someone who has a very strong reason to achieve what he wanted to do in his current job. Two main types of motivation are said to be intrinsic or extrinsic. Intrinsic motivation refers to motivation that comes from inside an individual rather than from any external or outside rewards, while extrinsic motivation is a construct that pertains whenever an activity is done in order to attain some separable outcome. If we as an individual doing something based on our willingness and eagerness, it is believed that we can achieve our objectives. It is true there are no limits to what we can achieve, but there are some key factors that can affect the motivation and this can become a limit to what can we achieve. It is clear that what affects the motivation is the motive itself and there is an important factor that can affect the employees’ motivation at work, which is compensation. Nevertheless, it is also believed since the compensation are made and controlled by organization and leader this can become the main factor of what can be achieved. Therefore, the ideal effort for leaders to motivate their employees is to get more concentrations on intrinsic motivation for making employees happy and enjoy, or convincing their self efficiency in working their tasks.